Under the Radar – Expatriate Children and Integration in Finland - Mari Korpela (Barn, 2023)
In policies and research, migrant children tend to be seen as underprivileged and vulnerable. This discourse ignores the more privileged migrant children, those labelled expatriates or third culture kids. Finland wants to attract skilled professionals from abroad. They are often accompanied by their children. Although the families typically intend to sojourn in the country temporarily, Finnish society tends to see them as ‘permanent immigrants’ who need to be integrated. This is visible in international schools that follow the national curriculum, including extensive Finnish language studies and exposure to Finnish culture. This article is based on an ethnographic study among expatriate children in an international school in a Finnish town. I ask how the integration aims affect the expatriate children’s lives, and how they navigate those aims. Using empirical examples, I elaborate on the contradiction between being a ‘privileged’ temporary expatriate child and being defined as an ‘underprivileged’ permanent immigrant.